DISSOLUTION ENHANCEMENT OF LANSOPRAZOLE USING COCRYSTALLIZATION - SURINI, SILVIA; NOVITASARI, DIAN; YANUAR, ARRY (International Journal of Applied Pharmaceutics, 2020)
Objective: Lansoprazole (LPZ) is a Biopharmaceutics Classification System Class II drug. It has low solubility and high permeability, so its rate of dissolution is a rate-limiting step for drug absorption. This study aimed to improve the dissolution rate of LPZ by forming cocrystals, using nicotinamide (NCT) as the conformer. Methods: Cocrystals of LPZ were produced using the solvent evaporation and solvent-drop grinding methods with a molar ratio of 1:1 and 1:2. The cocrystals were characterized using Fourier-transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), and differential scanning calorimetry (DSC). The solubility and dissolution of the LPZ cocrystals were examined in distilled water. Results: FTIR was used to confirm the formation of hydrogen bonds between LPZ and NCT. DSC and XRD studies showed the formation of crystals from cocrystals and a decrease of the melting point of the cocrystals. The dissolution study revealed that the cocrystals could increase the LPZ dissolution rate by up to 8.4-fold compared with pure LPZ. Conclusion: LPZ cocrystal formation with NCT was successful in increasing the dissolution rate of LPZ.